(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hepatocellular inflammation is a central feature of various liver diseases and is primarily mediated by cytokines, which are key regulators of immune and inflammatory responses. This article reviews the role of pro-inflammatory and anti-inflammatory cytokines in the pathogenesis of liver injury, focusing on their effects on hepatocyte function, immune cell recruitment, and fibrogenesis. Understanding the balance between these cytokines is crucial for the development of targeted therapeutic strategies aimed at controlling liver inflammation and preventing progression to chronic liver disease and cirrhosis.